2018
DOI: 10.1016/j.vhri.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

ERM for Health Care Organizations: An Economic Enterprise Risk Management Innovation Program (E2RMhealth care)

Abstract: risk economic assessment orientation is common among health care risk managers. Conclusion: We propose an ERM model for health care (Economic Enterprise Risk Management in Health Care) divided into four maturity levels and complemented by an implementation timeline. The model is accompanied by guidelines to orient the gradual implementation of ERM, including orientation to perform risk economic assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…The public sector is very vast and risk management can be challenging in the midst of increasing government projects, globalization and the consequence of inter-governmental transactions through the public sector (Woods et al 2017). The scope of responsibilities of auditors and those in charge of governance has increased tremendously in recent times, making it practically impossible to validate each activity that is performed in order to identify potential risk (Da Silva Etges et al 2018). Looking forward, we believe that an auditor's role in risk assessment should be supplemented with computerized internal control systems, segregation of duties, periodic review, and communication of timely information within the public sector in order to minimize the occurrence of risk and the impact on performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The public sector is very vast and risk management can be challenging in the midst of increasing government projects, globalization and the consequence of inter-governmental transactions through the public sector (Woods et al 2017). The scope of responsibilities of auditors and those in charge of governance has increased tremendously in recent times, making it practically impossible to validate each activity that is performed in order to identify potential risk (Da Silva Etges et al 2018). Looking forward, we believe that an auditor's role in risk assessment should be supplemented with computerized internal control systems, segregation of duties, periodic review, and communication of timely information within the public sector in order to minimize the occurrence of risk and the impact on performance.…”
Section: Discussionmentioning
confidence: 99%
“…That is why every organization implements risk assessment to identify threats and then manage them efficiently since business conditions are constantly changing Baumgartner and Rauter 2017;Da Silva Etges et al 2018). It is relevant to perform risk assessment to identify the internal and external threats that the entity is exposed to (Dementiev 2016;Dong et al 2017).…”
Section: The Concept Of Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors previously interviewed 15 hospital risk officers from Brazil and the USA and presented a novel model for healthcare risk management, the Economic Enterprise Risk Management innovation program for healthcare: E 2 RM healthcare [19]. This previous research identified qualitative differences in individual risk perception capabilities among risk managers from large and small hospitals based on personal background and whether the hospitals were associated with a school of medicine.…”
Section: Introductionmentioning
confidence: 99%